'Avatar journey mapping' for manufacturing firms to reveal smart-service opportunities over the product life-cycle. (20th October 2020) - West, Shaun; Stoll, Oliver; Mueller-Csernetzky, Petra
This paper presents a visual approach to supporting the development of new service opportunities that may have been overlooked in the original product service system design. The design of PSS increases in complexity compared to traditional product design/development since to create value in use, designers have to consider the usage of the product (Rapaccini et al., 2017). Using visual tools provides a common framework for discussions and service discovery (Stickdorn et al., 2018), in particular, identifying the intangible aspects of services. Three use cases were considered over their product life-cycles for the basis of the research: 1) glass-processing equipment; 2) printers; 3) aircraft. The combination of avatars and the journey mapping over different phases of the life-cycle provided a visual tool that revealed new services and provided a common platform for discussions.